The Relationship between Landing Error Scoring System Performance and Injury in Female Collegiate Athletes - Peter Lisman; Joshua N. Wilder; Joshua Berenbach; Enric Jiao; Bethany Hansberger (International Journal of Sports Physical Therapy)
# Background